2019
DOI: 10.3390/hydrology6040086
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Use Change and Its Impact on the Hydrology of Kakia and Esamburmbur Sub-Watersheds of Narok County, Kenya

Abstract: Narok town is one of the places in Kenya which experience catastrophic floods. Many lives have been lost and valuable property destroyed in recent years. Change in land use/land cover upstream of the town area may have contributed significantly to the severity and frequency of flooding events. Runoff, which contributes to floods in Narok town, comes from Kakia and Esamburmbur sub-catchments of Enkare Narok watershed. The objective of this study was to assess the impact of land use/land cover change on the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Land Use/Land Cover (LU/LC) change is one of the factors that directly affect the watershed hydrological cycle [3][4][5]. It has been widely accepted that human activities cause LU/LC change and have imposed a great impact on the hydrological processes and water resources of the watershed [6] For example, a study [1] showed that the water provision and the hydrological process decreased as consequence LU/LC change that was aggravated by significant increasing population pressure and development in Pennar Basin in India.…”
Section: Introductionmentioning
confidence: 99%
“…Land Use/Land Cover (LU/LC) change is one of the factors that directly affect the watershed hydrological cycle [3][4][5]. It has been widely accepted that human activities cause LU/LC change and have imposed a great impact on the hydrological processes and water resources of the watershed [6] For example, a study [1] showed that the water provision and the hydrological process decreased as consequence LU/LC change that was aggravated by significant increasing population pressure and development in Pennar Basin in India.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers usually study LULCC by investigating two or more maps produced at different times, for example, the work of Ptak & Ławniczak, 2012;Marie Mireille et al, 2019). Conventional maps and satellite images can be interpreted to study the causal effects of LULCCs and their implications for society and the environment (Kang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Landsat imagery to study LULCC is a widely known method and has been published in research reports worldwide (e.g. Lamichhane & Shakya, 2019;Marie Mireille et al, 2019;Al-Jiboori et al, 2020). LULCC may have positive and/or negative impacts on hydrological processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All processes related to defect in the earth's surface are influenced by human activities, which are responsible for the landform changes, especially during the environmental planning that involves public policies (Sucahyanto et al, 2018). The global development of urban areas due to an increase in population has continuously threatened natural dynamics, the availability of resources, and environmental quality (McGrane, 2016; Marie Mireille et al, 2019). Moreover, changes in land cover have caused some problems such as soil degradation which depends on intensity, pattern, and types of land cover change, namely depletion of nutrients, decrease in infiltration capacity and moisture content of the soil (Marie Mireille et al, 2019).…”
Section: Introductionmentioning
confidence: 99%